Deep Vein Arterialization (Dva) For No-Option Limb Salvage A Retrospective Study - Muhammad, Nisar; Elahi, Fazal; Masood, Ayesha; Ahmad, Muhaddis; Marwan, Muhammad (Journal of Neonatal Surgery, 2025)
Background: Chronic limb-threatening ischemia (CLTI) patients who prove to be unsuitable for conventional endovascular and surgical revascularisation are associated with high risks of major amputation and death. Deep vein arterialization (DVA) is a novel limb-salvage procedure to restore the inflow of arteries to the venous system. Objectives: To determine the clinical outcomes of deep vein arterialization among no-option CLTI patients, in terms of limb salvage, wound healing and safety of the procedure. Methodology: This retrospective study was conducted at Lady Reading Hospital, Peshawar, and Combined Military Hospital (CMH) Peshawar between January 2024 and January 2025, both tertiary-care vascular centers. The study included patients with Rutherford class 5–6 chronic limb-threatening ischemia who were deemed unsuitable for conventional revascularization. Percutaneous deep venous arterialization was performed using ultrasound-guided venous access, creation of an arteriovenous crossover, and deployment of stent-grafts to establish retrograde perfusion of the pedal venous plexus. Demographic data, comorbidities, procedural details, and follow-up outcomes were retrieved from medical records. Limb salvage at six months was the primary endpoint, while wound healing, pain control, and peri-procedural complications were evaluated as secondary outcomes. Results: A total of 75 patients underwent deep venous arterialization, with a mean age of 64.8 ± 9.6 years. Technical success was achieved in 68 patients (90.7%). At six-month follow-up, limb salvage was achieved in 54 patients (72.0%), while 21 patients required major amputation. Complete or near-complete wound healing was documented in 43 patients (57.3%), and relief of rest pain was reported by 49 patients (65.3%). When compared with historical controls receiving best medical therapy, the limb-salvage rate was significantly higher in the DVA cohort (72.0% vs. 38.0%, p < 0.001). Early complications were predominantly minor and managed conservatively, and no procedure-related mortality was observed. Conclusion: Deep venous arterialization represents a viable limb-salvage strategy for carefully selected patients with no-option chronic limb-threatening ischemia, offering improved limb-salvage rates with an acceptable safety profile when performed in specialized tertiary vascular centers.